Abstracts = Résumés (60, Spring 2012) (Labour / Le Travail, 2012)
English/French abstracts of articles in the Spring 2012 issue.
Keywords: Canada; EVACUATION & relocation, 1942-1945; Fisheries; JAPANESE; Labor; Legal status, laws, etc.; NEWFOUNDLAND & Labrador; SEX workers; SNOW crab fisheries